The Art of Co-Creation A Guidebook for Practitioners - Rill, Bryan R. (Springer Singapore, 2018)
This book illustrates how to design and implement co-creation, a powerful form of collective creativity that harnesses the potential of teams and can generate breakthrough insights. Skilled leaders and facilitators can utilize this approach to unleash the creative potential of their organizations. Drawing from years of applied research, the authors bring together insights from the fields of design and organizational development into an evocative and pragmatic "how-to" guidebook. Taking a human-centred rather than process oriented perspective, the book argues that experience design separates true co-creation from other forms of collective efforts and design thinking. Collective moments of creative insight emerge from the space between, an experience of flow and synchronicity from which new ideas spring forth. How to create and hold this space is the secret to the art of co-creation. Collective breakthroughs require stakeholders to undergo a journey from the world of their existing expertise into spaces of new potential. It requires leaders moving from a position of dominating space to holding the space for others, and developing core capacities such as empathy and awareness so that teams can engage each other co-creatively. This book uncovers the secrets of this journey, enabling process designers to develop more effective programs. .